Association Between TikTok Use and Insecurity Among Indonesian Generation Z: A Spearman Rank Correlation Study - Qori' Afiata Fiddina; Elok Kharismatul Ula; Vani Krismo Anggoro; Aninda Hawa Hanipah (Universitas Negeri Gorontalo, 2026)
The rapid growth of TikTok among Generation Z users has raised concerns about its psychological effects, particularly feelings of insecurity. This study examines the relationship between TikTok usage and insecurity among Generation Z using a quantitative correlational design. Data were collected via an online questionnaire from 121 Generation Z respondents aged 13–28 years who were active TikTok users and selected through purposive sampling. TikTok usage was measured through three indicators—attention, appreciation, and duration of use—while insecurity was measured through low self-esteem, anxiety, and fear of judgment by others. Both instruments demonstrated good validity and reliability, with Cronbach's Alpha values of 0.775 and 0.897, respectively. Data were analyzed using Spearman's rank correlation in SPSS. The results revealed a statistically significant, moderate positive correlation between TikTok usage and insecurity (r_s=0.541, p0.001, n=121), indicating that higher TikTok engagement is associated with greater insecurity, although this does not necessarily imply a direct causal effect. These findings support the view that intensive engagement with visually oriented social media platforms is associated with psychological factors such as low self-esteem, anxiety, and fear of negative evaluation among Generation Z. The study underscores the importance of balanced and self-regulated social media use and suggests further research into mediating factors such as social comparison and self-esteem.